Open Channel Hydraulics - Akan, A. Osman, author 364025; Iyer, Seshadri S., author 651024; ScienceDirect (Online service) 7722 (Amsterdam : Butterworth-Heinemann, 2021)
Open Channel Hydraulics, Second Edition provides extensive coverage of open channel design, with comprehensive discussions on fundamental equations and their application to open channel hydraulics. The book includes practical formulas to compute flow rates or discharge, depths and other relevant quantities in open channel hydraulics. In addition, it also explains how mutual interaction of interconnected channels can affect the channel design. With coverage of the theoretical background, practical guidance to the design of open channels and other hydraulic structures, advanced topics, the latest research in the field, and real-world applications, this new edition offers an unparalleled user-friendly study reference.